Conversations with great economist. Economic theory and economic policies in periods of high turbulence (2010)
In the 1970's there was a serious crisis in the world economy and a deep dissatisfaction with the state of economic theory. Between 1976 and 1979 Colombian economist Diego Pizano conducted a series of structured dialogues with some of the greatest economists of the second half of the 20th century, with the aim of discussing this situation. His project was supported from the outset by Professor Paul A. Samuelson from MIT. The result was a book on contemporary economic thought, which was published in Spanish by the Fondo de Cultura Económica of México in 1980. In 2009 the English version of this book was published in New York (Jorge Pinto books). In December 18th, 2009, The Brookings Institution of Washington DC decided to organize the launch of this book, because they thought it helps to understand the current crisis and is useful in rethinking economic theories and policies. This document brings together the presentations made on that occasion.